2017
DOI: 10.1055/s-0037-1606636
|View full text |Cite
|
Sign up to set email alerts
|

French Connection between Specialized and Routine Pediatric Surgical Care

Abstract: Introduction The success of modern pediatric surgery (PS) management has led to the recommendation of regional organization and coordination of PS departments. Although small units may obtain excellent results, there is evidence that a concentration to larger units is advantageous. In France, the centralization of PS has been discussed for the past 15 years. A new organization was finally achieved in 2010. The intent was to assure children prompt access to the level of care appropriate to the degree of their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…15,36 In France, the available data strongly suggest that centralization, specialization, and connections between specialized and routine pediatric surgical departments can greatly improve management of and outcomes in children. 34 In this study, it was demonstrated that efforts toward further centralization of pediatric surgery have already resulted in reduced morbidity and mortality. 34,38,39 These endeavors should be urgently pursued implementing the mission of ERNICA.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…15,36 In France, the available data strongly suggest that centralization, specialization, and connections between specialized and routine pediatric surgical departments can greatly improve management of and outcomes in children. 34 In this study, it was demonstrated that efforts toward further centralization of pediatric surgery have already resulted in reduced morbidity and mortality. 34,38,39 These endeavors should be urgently pursued implementing the mission of ERNICA.…”
Section: Discussionmentioning
confidence: 89%
“…34 In this study, it was demonstrated that efforts toward further centralization of pediatric surgery have already resulted in reduced morbidity and mortality. 34,38,39 These endeavors should be urgently pursued implementing the mission of ERNICA.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations